Cytotoxic Effect of the Paku Atai Merah (Angiopteris ferox Copel) Fraction on MCF-7 and HeLa Cells and its Compound Profile by GC-MS - Syamsu Nur; Andi Nur Aisyah; Endang Lukitaningsih; Rumiyati Rumiyati; Alfat Fadri; Marwati Marwati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Cancer is a condition of abnormal cell proliferation of tissue cells in the body that becomes malignant. It can attack other parts of the body and affect the normal function of the body organs. The sample used in this study was tubers of paku atai merah (Angiopteris ferox Copel), then extracted using 96% ethanol eluent to obtain a thick extract. The ethanolic extract of A. ferox was fractionated using column chromatography to get the active fraction to characterize the compound using thin-layer chromatography and gas chromatography-mass spectroscopy (GC-MS) and tested its cytotoxic effectiveness on MCF-7 and HeLa cancer cells. The results of this study were obtained from fractionation using the column chromatography method to get sub-fraction C and the results of compound characterization using GC-MS and obtained variations in the class of compounds contained in the sample: amino acids, glucosinolates, alkaloids, flavonoids, and terpenoids. Based on the cytotoxic effect test of sub-fraction C on MCF-7 cells, the results obtained moderate cytotoxic effects with an IC50 value of 61.027 µg/mL, and HeLa cells had an IC50 value of 521.03 µg/mL, which was categorized as having a weak cytotoxic effect. Based on the results obtained from this study, it can be concluded that sub-fraction C of A. ferox tubers has a cytotoxic effect on MCF-7 cells to be used as a reference for tracing pure compounds from A. ferox tuber.